A novel root hair mutant, srh1, affects root hair elongation and reactive oxygen species levels in wheat - Tsang, Ian; Thomelin, Pauline; Ober, Eric S.; Rawsthorne, Stephen; Atkinson, Jonathan A.; Wells, Darren M.; Percival-Alwyn, Lawrence; Leigh, Fiona J.; Cockram, James (Frontiers in Plant Science, 2024)
Background Root hairs are single-celled projections on root surfaces, critical for water and nutrient uptake. Here, we describe the first short root hair mutant in wheat (Triticum aestivum L.), identified in a mutagenized population and termed here short root hair 1 (srh1). Results While the srh1 mutant can initiate root hair bulges, lack of subsequent extension results in very short root hairs. Due to its semi-dominant nature, heterozygous lines displayed intermediate root hair lengths compared to wild-type. Bulked segregant analysis in a BC1F3 segregating population genotyped via exome capture sequencing localized the genetic control of this mutant to a region on the long arm of chromosome 3A. Via RNA sequencing and bioinformatic analysis, we identified two promising candidate genes. The first was a respiratory burst oxidase homolog (RBOH) encoding gene TaNOX3-A, orthologous to RBOH genes controlling root hair elongation in rice (OsNOX3) and maize (ZmRTH5), that carries a missense mutation in a conserved region of the predicted protein. RBOHs are membrane bound proteins that produce reactive oxygen species (ROS) which trigger cell wall extensibility, allowing subsequent root hair elongation. Notably, reduced ROS levels were observed in srh1 root hair bulges compared to wild-type. The second candidate was the calreticulin-3 encoding gene TaCRT3-A, located within the wider srh1 interval and whose expression was significantly downregulated in srh1 root tissues. Conclusions The identification of a major effect gene controlling wheat root hair morphology provides an entry point for future optimization of root hair architecture best suited to future agricultural environments.